Monitoring South-South cooperation (May to September 2016) - Surasky, Javier (Revista Española de Desarrollo y Cooperación, 2023)
South-South Cooperation is facing a turning point moment: to live in the past remembering what it was, or start assuming that things have changed, and then make over to remain relevant./p>